Delignification of oil palm empty fruit bunch via ultrasound-assisted deep eutectic solvent pretreatment. Issue 1 (March 2020) - Quek, Joo Ding; Lee, Kiat Moon; Lim, Steven; Tey, Wah Yen; Kang, Hooi-Siang; Quen, Lee Kee
Abstract: Lignin is the complex organic polymers contain in lignocellulosic biomass, acting as structural support of the biomass. Its presence making the biomass recalcitrance to bioprocessing. Therefore, pretreatment is essential in removing the lignin content to enhance the sugar extraction and bioethanol production from lignocellulosic biomass. In this work, pretreatment of oil palm empty fruit bunch (OPEFB) using ultrasound-assisted deep eutectic solvents (DESs) was performed. Three types of DESs, namely choline chloride-lactic acid (ChCl-LA), choline chloride-glycerol (ChCl-G) and choline chloride-urea (ChCl-U) in delignification were studied. The pretreatment was conducted with the presence of ultrasonication. The DESs recyclability were also performed in this work. ChCl-LA exhibited the best delignification properties, in which ChCl-LA pretreated OPEFB had the lowest total lignin content of 18.8%, followed by ChCl-U (19.4%) and ChCl-G (21.2%). All the three DESs were successfully recycled with slight decrement in delignification performance after two recycles. The recyclability of the DESs would improve the economic feasibility of the pretreatment process.